Rewiring the injured CNS: lessons from the optic nerve - Benowitz, Larry (2007)
The optic nerve offers a number of advantages for investigating mechanisms that govern axon regeneration in the CNS. Although mature retinal ganglion cells (RGCs) normally show no ability to regenerate injured axons through the optic nerve, this situation can be partially reversed by inducing an inflammatory response in the eye. The secretion of a previously unknown growth factor, oncomodulin, along with co-factors, causes RGCs to undergo dramatic changes in gene expression and regenerate lengthy axons into the highly myelinated optic nerve. By themselves, strategies that counteract inhibitory signals associated with myelin and the glial scar are insufficient to promote extensive regeneration in this system. However, combinatorial treatments that activate neurons' intrinsic growth state and overcome inhibitory signals result in dramatic axon regeneration in vivo. Because of the ease of introducing trophic factors, soluble receptors, drugs, or viruses expressing any gene or small interfering RNA of interest into RGCs, this system is ideal for identifying intracellular signaling pathways, transcriptional cascades, and ligand-receptor interactions that enable axon regeneration to occur in the CNS and to develop means to augment this process.